PENGEMBANGAN RUBRIK PENILAIAN KETERAMPILAN DAN SIKAP ILMIAH MATA PELAJARAN FISIKA KURIKULUM 2013 DI KELAS X SEKOLAH MENENGAH ATAS - Selly Noverina; Taufiq .; Ketang Wiyono (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
It has been successfully develope dan assessment rubric scientific skills  and attitudes. This study aim stop produce the  skills and attitude assessment rubric scientifically valid and practical. The research method use dis a research method development (development research) by applying 4D model sthat include phase define, design, develop, desseminate. Rubric assessment skills and scientific attitudes declared in valid based on the expert valid ation stage expert review with a percentage of 3.58%  for skills assessment rubrics and assessment rubrics 3.74% for the scientific and practical attitude on stage one-to-one with a percentage of 80.91% and 83.79% and a small group with a percentage of 84.73% and 84.75% were tested in senior high school  two state palembang. Based on the results of the study it can be concluded rubric assessment skills and scientific attitudes are ready for use.